Microchannel Heat Sink with High Thermal Conductivity Path for Diode Partially End-Pumped Slab Laser. Issue 1 (January 2021) - Guo, Zhanfeng; Wu, Yongjin; Sun, Yunna; Wang, Yan; Ding, Guifu
Abstract: The thermal effect of diode pumped solid-state laser (DPSSL) has always been a main problem limiting the further improvement of laser performance. In this paper, based on the special heat load distribution of the laser crystal of diode partially end-pumped slab (Innoslab) laser, a multi-stage manifold rectangular microchannel heat sink (MCHS) with high thermal conductivity path (HTCP) is designed. The multi-stage manifold provides the MCHS more fluid-solid heat transfer area near the heat gathering area, while the HTCP provides a path for heat transmission from pump end to the body of MCHS. According to simulation calculation, the highest temperature of laser crystal has been reduced by nearly 50? due to the addition of HTCP. Then the MCHS is fabricated by MEMS technology and the laser crystal is replaced by simulated heat source. Compared with the MCHS without the HTCP, the thermal resistance of the MCHS with HTCP is reduced by 6.4%, which proves the effectiveness of HTCP in heat dissipation of Innoslab laser crystal.